Neglected Heterogeneity and Dynamics in Cross-Country Savings Regressions. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This paper examines the extent to which conclusions of cross-country studies of private savings are robust to allowing for the possible heterogeneity of savings behavior across countries and the inclusion of dynamics. It shows that neglecting heterogeneity and dynamics can lead to misleading inferences about the key determinants of savings behavior. The results indicate that among the many variables considered in the literature only the fiscal variables-the general government surplus as a proportion of GDP and the ratio of government consumption to GDP-are important determinants of private savings rates in the industrial countries in the post-World War II period.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet